2021
DOI: 10.3390/ijerph182111025
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors and Endometriosis

Abstract: Endometriosis is a common disease, affecting up to 60–80% of women, with pelvic pain or/and infertility. Despite years of studies, its pathogenesis still remains enigmatic. Genetic, hormonal, environmental, and lifestyle-related factors may be involved in its pathogenesis. Thus, the design of the review was to discuss the possible role of environmental factors in the development of endometriosis. The results of individual studies greatly differ, making it very difficult to draw any definite conclusions. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…In two independent reviews, both Parazzini et al 19 and later Osmanlioglu et al 22 agreed that evidence supporting a significant association between diet and endometriosis is equivocal. Polak et al 21 could not take out any significant conclusions about the relation between…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In two independent reviews, both Parazzini et al 19 and later Osmanlioglu et al 22 agreed that evidence supporting a significant association between diet and endometriosis is equivocal. Polak et al 21 could not take out any significant conclusions about the relation between…”
Section: Discussionmentioning
confidence: 96%
“…A consequent important issue is to establish whether and how promoters of inflammation could influence endometriosis risk 15,16 . It is not surprising that modifiable lifestyle factors, such as diet, caffeine, environment, and smoking, all factors possibly associated with inflammation, have been explored in this regard [17][18][19][20][21][22][23][24] . Alcohol has already gained a certain attention.…”
Section: A Systematic Review and Meta-analysis On Alcohol Consumption...mentioning
confidence: 99%
“…Clinical and experimental data also indicate that exposure to EDCs affects fertility by interfering with multiple processes, including folliculogenesis, steroidogenesis, ovulation, fertilization, and gestation, which means EDCs disrupt ovarian function and fertility ( Figure 1 ). Numerous studies have suggested that exposure to EDCs may increase the incidence of uterine fibroids by promoting estrogen-dependent hyperplasia of the myometrium, endometriosis, premature ovarian failure, and polycystic ovary syndrome (PCOS) [ 49 , 50 , 51 , 52 ]. In addition, exposure to EDCs during early gestation disrupts intrauterine implantation and uterine reception, leading to implantation failure [ 53 ].…”
Section: Disease Endpoints In Relation To Edcsmentioning
confidence: 99%
“…Koike et al showed that in mice exposed to DES, constant expression of the lactoferrin and EGF genes can be observed in the vagina and uterus [ 63 ]. Furthermore, Wang et al hypothesized that EGF could stimulate endometriosis cell proliferation by activating the Ras/Raf/MEK/ERK pathway [ 72 , 73 , 74 ].…”
Section: Environmental Impactmentioning
confidence: 99%